A Quantitative Evaluation of the Barriers Hindering the Growth of Small Sized Enterprises in a Developing Economy - Kharub, Manjeet (My University, 2012)
ABSTRACT Global competition, technological changes, changing economies and demanding customers are creating a more knowledge-intensive, turbulent, complex and uncertain environment. In such a challenging, volatile and hyper-competitive environment, any manufacturing firm, which is able to compete on all dimensions of competitive priorities such as fast delivery, high quality, low price, volume and product flexibility can be considered as a competitive firm. Organizations should develop core competencies, which will give them a competitive advantage over their competitors in meeting fast changing market requirements. The foundation of organizational competitiveness has shifted from physical and tangible resources to knowledge. Micro, Small, and medium enterprise (MSMEs) development is identified by the government as a priority in creating jobs to solve the high unemployment rate. MSMEs play a particularly important role in a country’s economy, because of their number and because of their large share of the workforce involved. The government has for many years carried out a variety of programmes to support these enterprises, although not great deals of these programmes are known by MSMEs. In India, MSMEs lag well behind in terms of know-how, number of technical employees, skill levels, capital investment to support their activities, and access and ability to take advantage of modern technologies. As in most countries they find it difficult to obtain financing. Apart from the lack of funding, MSMEs appear to suffer from a lack of information and efficient production technologies, scant use of management and control systems, inability to access consulting services and other related deficiencies. Therefore the need for this study is to set an action plan for MSMEs to increase their efficiency, to sustain themselves and guard against factors contributing to failure. In order to carry out this plan, there is a need to understand the MSMEs operations and the role they play in the global economy. Furthermore, it is of particular importance to understand the factors contributing to the failure of MSMEs since it is suggested that a large percentage of MSMEs mostly fail within the first five years of their operation. The pressure on organizations to adapt to new technologies and external threats requires resourcefulness, creativity and innovation by combined effort of all departments (Finance, HRM, Marketing etc.). The organizations should develop learning habits in their organization to overcome the problems faced by them in the competitive environment at the global as well as local front. x The report is divided into five main chapters; the first chapter introduces MSMEs, their importance, and contributions etc. The second chapter explores the literature regarding factors that lead to the failure of MSMEs. The third chapter puts forward the methodology to be adopted for carrying out the research. The fourth chapter explores the status of each factors, the classification of manufacturing units each factors, the correlation analysis between the input and output factors. This descriptive and empirical analysis has been carried out for seven main factors identified through an extensive literature review. These factors include Lack of ‘Strategic Financial management’, ‘Entrepreneurship and managerial skills’, ‘Human resource management’, ‘Planning and Decision making, ‘Marketing Research’, ‘Infrastructure as well as Government Support’, In chapter forth study followed a quantitative approach by gathering data from 25 small firms (cutting tool industries) in the region of Patiala, Punjab. Assumed factors leading to their failure are characterized by ‘Lack of Strategic Financial management’, ‘Lack of Entrepreneurship and managerial skills’, ‘Lack of Human Resource management’, ‘Lack of Planning and Strategy making, ‘Lack of Marketing Research’, ‘ Lack of Infrastructure and Technological know-how’, ‘Lack of Government Support’. The chapter fifth chapter present the result major conclusions of work.
Keywords: Barriers, MSMEs; HRM Practices